2011
DOI: 10.2337/dc10-1602
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parenting Style in Achieving Metabolic Control in Adolescents With Type 1 Diabetes

Abstract: OBJECTIVETo examine the role of parenting style in achieving metabolic control and treatment adherence in adolescents with type 1 diabetes.RESEARCH DESIGN AND METHODSParents of 100 adolescents with type 1 diabetes completed assessments of their parenting style and sense of helplessness. Parents and patients rated patient adherence to the treatment regimen. Glycemic control was evaluated by HbA1c values.RESULTSAn authoritative paternal parenting style predicted better glycemic control and adherence in the child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 13 publications
4
72
3
2
Order By: Relevance
“…Maternal and paternal parent–child relationships characterized by warmth, support, sensitivity, acceptance, and independence encouragement are associated with greater quality of life [29], adherence [21, 27, 30, 31], glycemic control [19, 21, 29, 30], and self-efficacy [14•] as well as lower frequency of diabetic ketoacidosis [32] and lower levels of externalizing behaviors [14•] in adolescents. Several studies have indicated that children of parents who are both warm and sensitive while maintaining high expectations for adolescents’ behavior were in better glycemic control [33, 34] and displayed more self-care behaviors (e.g., BGM, giving insulin shots, not skipping meals) [34]. Additionally, adolescents of parents who balanced rule setting with granting freedom reported lower stress and were in better glycemic control [35].…”
Section: Quality Of Involvementmentioning
confidence: 99%
“…Maternal and paternal parent–child relationships characterized by warmth, support, sensitivity, acceptance, and independence encouragement are associated with greater quality of life [29], adherence [21, 27, 30, 31], glycemic control [19, 21, 29, 30], and self-efficacy [14•] as well as lower frequency of diabetic ketoacidosis [32] and lower levels of externalizing behaviors [14•] in adolescents. Several studies have indicated that children of parents who are both warm and sensitive while maintaining high expectations for adolescents’ behavior were in better glycemic control [33, 34] and displayed more self-care behaviors (e.g., BGM, giving insulin shots, not skipping meals) [34]. Additionally, adolescents of parents who balanced rule setting with granting freedom reported lower stress and were in better glycemic control [35].…”
Section: Quality Of Involvementmentioning
confidence: 99%
“…17 Another factor that seems to interact with age is the level and style of parental involvement as the children age: studies have shown that parental involvement and its effectiveness in maintaining glycemic control vary over time as the young patients age. 21 Another interesting aspect that is given much less attention in the existing literature is later age transitions: While children and adolescents with T1DM have been the subject of substantial investigation, young adults and their interactions with their peers, families, and other social circles in light of their condition received much less attention. A recent position paper 12 suggests that the transition from childhood and adolescence -often characterized by higher levels of parental supervision -into adulthood (often associated with moving out of home, increased independence) is a sensitive point where transition of care and support is inadequately understood and practiced.…”
Section: Age Of Patientmentioning
confidence: 99%
“…35 Higher levels of paternal support is hypothesized to minimize maternal sense of helplessness and decrease diabetes-related verbal conflict between maternal caregivers and youth. 36,37 Researchers have also identified that both maternal and paternal caregivers may have different, but equally important, roles in supporting youth's diabetes management. 37,38 Specifically, maternal and paternal caregivers who have more positive relationships with their child and demonstrate regular monitoring also have youth with better adherence.…”
Section: Familymentioning
confidence: 99%
“…36,37 Researchers have also identified that both maternal and paternal caregivers may have different, but equally important, roles in supporting youth's diabetes management. 37,38 Specifically, maternal and paternal caregivers who have more positive relationships with their child and demonstrate regular monitoring also have youth with better adherence. 38 Behavioral involvement in daily diabetes care tasks by maternal caregivers was associated with better adherence, whereas father behavioral involvement in daily diabetes care tasks was related to poorer adherence among youth with type 1 diabetes.…”
Section: Familymentioning
confidence: 99%
See 1 more Smart Citation